PRIMARY IMMUNODEFICIENCY CONDITIONS - Ibragimova Nadiya Sabirovna; Babakhanova Farizakhon Shekhrozovna (Web of Journals Publishing, 2024)
One of the most pressing problems in medicine today is the growth of immune-dependent pathologies, i.e. diseases based on immunopathological mechanisms [1, 7]. Primary immunodeficiencies are a large group of severe, genetically determined diseases, the cause of which is a violation of the body’s immune response cascade [2, 4]. Diseases with immunopathological conditions are characterized by early chronicity, reluctance to traditional methods of therapy and the need for immunorehabilitation [1]. This article is devoted to studying the problem of diagnosis and treatment of primary immunodeficiencies, with the aim of reducing the mortality of patients and improving their quality of life.
Keywords: primary immunodeficiency, main groups, autoimmune diseases, immunoglobulins, treatment tactics.